ANALYSIS OF FACTORS AFFECTING FIRM VALUES WITH CSR DISCLOSURE AS MODERATING VARIABLES IN MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) IN 2014-2017 - Tarihoran, Anita (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to analyze the effect of Leverage, Profitability, Firm Size, Institutional Ownership and Independent Commissioners on Firm Value with CSR Disclosure as a Moderating variable in companies listed on the Indonesia Stock Exchange in 2014 - 2017.The population in this study amounted to 160 companies. The sampling method used in this study was purposive sampling method and obtained as many as 58 sample companies that were the object of research. This type of research is quantitative descriptive by testing the classical assumptions and the Multiple Regression Analysis (MRA) test that uses two regression equations. The analysis shows that simultaneously all independent variables significantly affect the Firm Value. Partially, Leverage has a negative effect on Firm Value, Profitability and Firm Size has a significant positive effect on Firm Value. While Institutional Ownership and Independent Commissioners have no significant effect on Firm Value. CSR disclosure weakens the relationship between independent variables and firm value.